When Islamic Spirituality Meets Magic: Aḥmad ibn ‘alī al-būnī (d. 622/1225) and the Science of Letters - Lien Iffah Naf'atu Fina (Universitas Islam Negeri Mataram, 2016)
This paper attempts to provide a balanced and comprehensive reading of al-Būnī, who is mainly known as a scholar of Islamic magic, instead of a Sufi. This is because his name and works are widely known and referred in the Islamic world even into the present, including in Indonesia. To accomplish this agenda, this paper examines al-Būnī’s ideas on the science of letters across his works in order to determine how they are rooted in the principles of Islamic spiritualy. From the examination of al-Būnī’s science of letters, it can be seen that Islamic spirituality underlies his works: in the centrality of God and in sober Sufi devotions such as dhikr and fasting, as the complement of the magical materials. Furthermore, while he was a respectable Sufi at that time, he also wrote books in which he explored the Arabic letters primarily from an Islamic spirituality approach. By combining magical practice and Islamic spirituality, al-Būnī provided practical Sufism for the masses. DOI: http://dx.doi.org/10.20414/ujis.v20i2.814